Modernity of the Bataknese in Tapanuli during the Dutch Colonial and Japanese Occupation Period - Tanjung, Ida Liana (Paramita: Historical Studies Journal, 2024)
Abstract: This paper examines the modernity of the Batak people during the Dutch colonial period and Japanese occupation. The data utilized were derived from both oral and written sources, and a historical research methodology was employed, comprising source collection, source criticism, interpretation, and explanation. The focus of this study revolves around the evolution of Batak modernity, initiated through the introduction of Western education by the colonial administration and missionary endeavors commencing in the mid-19th century. This educational trend persisted during the ethical policy era of the 20th century, bringing modernity into the lives of the Batak people. Stereotypes depicting the Batak as an uncivilized and cannibalistic ethnic group gradually diminished with the increasing number of educated Batak individuals. During the Dutch colonial period, the Batak people had already formed a modern elite group that embraced Dutch colonial modernity. However, the modernity of this Batak elite was characterized by ambiguity, as they simultaneously became part of modernity while preserving Batak characteristics and traditions. In 1942, when Japan took over Tapanuli, the Batak people became more involved in practical politics with the Japanese. This phase was marked by a heightened interest among the Batak people in joining the military. The military education provided by the Japanese was effectively utilized by the Batak people, resulting in the emergence of Batak military leaders in Tapanuli. Therefore, it can be concluded that education served as the pathway for the Batak people to embrace modernity and attain positions of power.Paper ini mengkaji tentang modernitas orang-orang Batak pada masa Kolonial Belanda dan Pendudukan Jepang.  Data-data yang digunakan dalam tulisan ini diperoleh dari sumber lisan dan tulisan melalui  penelitian sejarah. Adapun metode yang digunakan adalah metode sejarah yang terdiri dari pengumpulan sumber, kritik sumber, interpretasi dan eksplanasi. Modernitas orang Batak yang menjadi objek dalam penelitian ini berawal dari diperkenalkannya pendidikan barat oleh pemerintah kolonial dan zending sejak pertengahan abad ke-19. Pendidikan ini terus berkembang pada masa masa politik etis di abad ke-20 yang menghadirkan modernitas dalam kehidupan orang-orang Batak. Stereotipe tentang orang Batak sebagai kelompok etnis yang tidak beradab dan kanibal lambat laun mulai menghilang dengan  meningkatnya  jumlah orang Batak yang berpendidikan. Pada masa kolonial Belanda, orang-orang Batak  telah menciptakan kelompok elit modern yang mengadopsi modernitas kolonial Belanda. Namun, modernitas elit modern Batak bersifat ambigu. Di satu sisi mereka menjadi bagian dari modernitas tetapi di sisi lain mereka masih memelihara karakteristik dan tradisi Batak. Pada tahun 1942, saat Jepang mengambil alih Tapanuli, orang-orang Batak lebih banyak terlibat dalam  politik praktis dengan Jepang. Fase ini ditandai dengan meningkatnya minat orang Batak untuk bergabung di militer. Pendidikan militer disediakan Jepang dimanfaatkan dengan baik oleh orang Batak. Pendidikan ini menghasilkan pemimpin-pemimpin militer orang Batak di Tapanuli.  Dengan demikian dapat disimpulkan bahwapendidikan menjadi jalan bagi orang Batak untuk menjadi modern dan memperoleh kekuasaan.